Association of Circulating Osteopontin Levels With Lower Extremity Arterial Disease in Subjects With Type 2 Diabetes Mellitus: A Cross-Sectional Observational Study. (June 2020) - Eleftheriadou, Ioanna; Tsilingiris, Dimitrios; Tentolouris, Anastasios; Mourouzis, Iordanis; Grigoropoulou, Pinelopi; Kapelios, Christos; Pantos, Constantinos; Makrilakis, Konstantinos; Tentolouris, Nikolaos
Osteopontin (OPN) is involved in the atherosclerotic and inflammatory process. In this article, we examined the relationship between circulating OPN levels with lower extremity arterial disease (LEAD) in individuals with type 2 diabetes mellitus (T2DM). Seventy individuals with T2DM and 66 individuals without T2DM were recruited. Diagnosis of LEAD was based on the absence of triphasic waveform on the pedal arteries. Plasma OPN levels were determined by Luminex Multiplex immunoassay. LEAD was present in 34 (48.6%) patients with T2DM. In the diabetes cohort, individuals with LEAD had higher plasma OPN concentrations than those without LEAD (geometric mean [95% confidence intervals]; 43.4 [37.5-50.4] vs 26.1 [22.9-29.8] ng/mL, respectively, P < .001). Multivariable analysis showed that presence of LEAD independently associated with higher OPN levels in subjects with T2DM, with marginal statistical significance ( P = .049). In both cohorts, plasma OPN concentrations were negatively associated with ankle-brachial index values ( P < .05). In the total sample, there was a gradual increase of OPN levels across subgroups with triphasic, biphasic, and monophasic/blunted waveforms ( P < .001). In conclusion, plasma OPN levels are associated with the presence and severity of LEAD in subjects with T2DM. Further studies are needed to investigate the role of OPN in the pathogenesis and progression of LEAD.